ANALISIS PENDAPATAN PETANI DAN NILAI TAMBAH PENGOLAHAN PRIMER KOPI ROBUSTA DI KECAMATAN DAWE KABUPATEN KUDUS - Estikasari, Maya Estikasari; Nurfadillah, Suryani; Budiraharjo, Kustopo (MEDIAGRO, 2023)
Primary processing is the most important aspect of enhancing the added value of Robusta Coffee, but some farmers didn't. This study aims to analyze the reasons why Robusta coffee farmers sell in the form of cherry or beans coffee, analyze the compare in farmers income that sells coffee cherry and beans, and analyze the added value of coffee beans. The research was conducted in January-February 2023 in Dawe District, furthermore two villages were selected with criteria for the largest Robusta Coffee land area in Japan Village and Colo Village. This research used a survey method. The determination of the sample using simple random sampling. Furthermore, the sample size in each group is the determination of the sample proportional random sampling with 61 farmers selling coffee cherry and 44 farmers selling coffee beans. The analytical method used descriptive, income, and Hayami's added value analysis. Income difference analyzed by Independent Sample t-Test. The result showed the main reason farmers sell coffee cherry was the needed quick refund of their capital. While the main reason farmers sell coffee beans was highly profitable. The income of farmers who sell coffee cherry and coffee beans is IDR 16.433.627/ha/year and IDR 23.230.330/ha/year with an average land area of 0,84 ha and 0,90 ha. The income of farmers who sells coffee beans is differ significantly from those who sells cherry. The added value of primary processing is IDR 1.530/kg with a medium category value added ratio of 19,03%.Keywords: Coffee cherry, green beans, Hayami, income, primary processing